Planning for the Realization of the Demographic Dividend and Leveraging Iran\'s Demographic Dividend Window in the Health Sector - Alireza Amini; Naeim Shokri; Mohammad Mesgarpour Amiri (Rāhburdhā-yi Mudīriyyat dar Niẓām-i Salāmat)
Background: Iran's economy is among those experiencing a "demographic dividend window," a period extending to the next two decades (2040). Capitalizing on this golden opportunity plays a crucial role in the country's economic and social development. This study aims to identify strategies and solutions, and propose implementable health sector programs to realize this demographic dividend. Methods: This qualitative study employed structured interviews with 11 health experts, purposively sampled in 2021. Following a presentation of demographic theory, experts were asked to explain strategies and solutions for achieving demographic dividend in the health sector. Interview content was analyzed using axial coding with MaxQDA 2018 software. Results: Based on research conducted in the field of health policy, including expert interviews and a review of World Health Organization documents, 4 key areas for achieving demographic dividend in health are: "reducing premature mortality," "reducing disability caused by diseases and accidents," "increasing the quantity and quality of births," and "improving the quality of life for the elderly." Target setting and monitoring for achieving the demographic dividend are facilitated by 11 indicators across the following areas: monitoring of leading causes of death (2 indicators), reproductive and maternal health (2 indicators), health financing (3 indicators), public health and sanitation (2 indicators), and access to healthcare (2 indicators).